2001
DOI: 10.1007/s005950170117
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma Arising in the Pancreas 17 Years After Primary Excision of a Choledochal Cyst: Report of a Case

Abstract: We report herein the case of a 42-year-old woman in whom a pancreatic carcinoma was found 17 years after excision of a choledochal cyst with Roux-en-Y hepaticojejunostomy. Although the incidence of biliary carcinoma associated with choledochal cyst is high, reports of cancer developing in the remaining intrapancreatic biliary tract or pancreas in patients who have previously undergone primary excision of a choledochal cyst are extremely rare. Long-term follow-up is recommended even for patients who have underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…There have been some case reports of patients with CDB in whom cancer developed in the bile duct remnant at the distal end of a cystic-dilated extrahepatic duct after the resection of an extrahepatic bile duct. Eriguchi et al 11 reported such a case that developed 17 years after the excision of a choledochal cyst. Kurokawa et al 12 reported a patient who developed cancer of the pancreatic head 3 years after the excision of a choledochal cyst, as well as referring to four other reported cases that developed cancer after the excision of a choledochal cyst.…”
Section: Discussionmentioning
confidence: 96%
“…There have been some case reports of patients with CDB in whom cancer developed in the bile duct remnant at the distal end of a cystic-dilated extrahepatic duct after the resection of an extrahepatic bile duct. Eriguchi et al 11 reported such a case that developed 17 years after the excision of a choledochal cyst. Kurokawa et al 12 reported a patient who developed cancer of the pancreatic head 3 years after the excision of a choledochal cyst, as well as referring to four other reported cases that developed cancer after the excision of a choledochal cyst.…”
Section: Discussionmentioning
confidence: 96%
“…Reports on cholangiocarcinoma derived from remnant intrapancreatic bile duct are rare. To the best of our knowledge, there are only 6 other reported cases, which include 1 man and 5 women (average age: 42.7 years, range: 27-68; table 2) [4,[7][8][9][10][11], and all of these patients underwent surgery for intrapancreatic cholangiocarcinoma. Four of 6 cases had postoperative mortality after a short term of 9-16 months (average: 12.3 months).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports of malignant transformation in the bile duct, both proximal and distal, after cyst excision, even many years after initial treatment, were published, which outline the importance of long term follow-up [70][71][72][73][74][75]. Long-term survival in patients, who developed malignancy is rare and equals that of the general population with cholangiocarcinoma [63,76].…”
Section: Outcome and Prognosismentioning
confidence: 99%